Prevalence Of Plasmodium Falciparum And P. Vivax Infection In Malaria Patients Of Matiranga, Khagrachhari (Dhaka University Journal of Biological Sciences, 2012)
The investigation was performed to study the different growth stages of malarial parasite found in the peripheral blood of malaria patients of Matiranga, Khagrachhari. Rapid diagnostic test (RDT) was used to screen positive patient. The early trophozoite stages were measured 1.3 ? 1.6 μm, late trophozoites 2.5 ? 2.9 μm in diameter, microgametes 9?10 μm by 2 ? 3 μm and macrogametes 11 ? 12 μm by 2 ? 3 μm for Plasmodium falciparum. The early trophozoites 2.2 ? 3.0 μm and late trophozoites 3.3 ? 5.0 μm in diameter for Plasmodium vivax were measured. The patients of age group 1 (0 ? 10 years) were more (25%) vulnerable to the severe malaria (++++), which was 10% of the total infection, while only 10% patients of age group 2 (> 10 years) were suffering from severe form, only 0.6% of the total infection. In age group 1 (0 ? 10 yrs), + infection was 30%, ++ was 40% and +++ was 5%. In age group 2 (> 10 years), + infection was 26.66%, ++ 56.67% and +++ 6.67%, respectively. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9747 DUJBS 2012 21(1): 79-85